PENGARUH MODEL TIPE INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR - Ferryansyah Ferryansyah; Indra Gormaks Pauba (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2021)
AbstractThe purpose of this research is to clarify first to see the influence of the model (IOC and Conventional) on mathematics learning outcomes. Second, look at the influence of motivation (high and low) on students' mathematics learning outcomes. Third, look at the effect of interaction with the model (IOC and Conventional) and student motivation on students' mathematics learning outcomes. The activity was carried out at SMPN 5 Tarakan in the even semester of 2019-2020. The study used a quasi-experiment with 2x2 factorial. The population is class IX students of SMPN 5 Tarakan. Samples were taken by simple random sampling. Class IX-1 is the experimental class and class IX-7 is the control class. Data were collected using a description test and questionnaire questions for motivation to learn mathematics. Descriptive methods include the mean and standard deviation. Inference method by analyzing the variance of two factors. The analysis at the 5% significance level shows that the model (IOC and Conventional) has a p-value of 0.036, which means that it affects students' mathematics learning outcomes. Motivation to learn mathematics has an effect on student learning outcomes at a p-value of 0.000. And there was no effect of mutual interaction between the model and motivation on the mathematics learning outcomes of students in class IX of SMPN 5 Tarakan with a p-value of 0.222.Keywords: Inside Outside Circle (IOC), Student’s Learning Achievement, Student’s Learning Motivation.AbstrakTujuan penelitian adalah memperjelas pertama melihat adanya pengaruh model (IOC dan Konvensional) terhadap hasil belajar matematika. Kedua, melihat adanya pengaruh motivasi (tinggi dan rendah) pada hasil belajar matematika siswa. Ketiga, melihat adanya pengaruh interaksi bersama model (IOC dan Konvensional) dan motivasi siswa pada hasil belajar matematika siswa. Kegiatan dilaksanakan di SMPN 5 Tarakan pada semester genap 2019-2020. Penelitian menggunakan eksperimen semu dengan faktorial 2x2. Populasi adalah siswa kelas IX SMPN 5 Tarakan. Sampel diambil dengan cara simple random sampling. Kelas IX-1 adalah kelas eksperimen dan kelas IX-7 adalah kelas kontrol. Data dikumpulkan menggunakan tes uraian dan pertanyaan angket untuk motivasi belajar matematika. Metode deskriptif meliputi mean dan standar deviasi. Metode inferensi dengan menganalisis varians dua faktor. Analisis pada taraf signifikansi 5% menunjukkan bahwa model (IOC dan Konvensional) memiliki p-value 0,036 yang artinya berpengaruh terhadap hasil belajar matematika siswa. Motivasi belajar matematika berpengaruh terhadap hasil belajar siswa pada p-value 0,000. Dan tidak ditemukan adanya pengaruh interaksi bersama antara model dan motivasi pada hasil belajar matematika siswa di kelas IX SMPN 5 Tarakan dengan p-value 0,222.